PERENCANAAN SDM SEBAGAI UPAYA UNTUK MENGANTISIPASI PERUBAHAN LINGKUNGAN YANG DINAMIS - Rahadhini, MD - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2005)
Abstract The fundamental change in the business environment demands the company be capable of adapting in the growth of dynamic and competitive business environment. The selection and implementation of the perfect business strategy will be strongly determined by the human resources quality who take an important role in doing the operational activities of the company, like planning and running the determined business strategy. Human resources is a critical asset organization which includes not only in company philosophy but in process of strategic plan as well. To meet the phenomenon, it is very necessary to have the human resources planning to obtain the accuracy of number, place, and time that can drive benefit wheter to individual or organization in the long term. Through the human resources planning, it is expected that the organization is be able to organize and manage its human resources to elevate the competence and quality of human resources, so that there will be competitive advantage to win the competition which has been more and more competitive. Keywords: human resource planning, business environment, strategic plan